Virtual Fence Responses Are Socially Facilitated in Beef Cattle - Keshavarzi, Hamideh; Lee, Caroline; Lea, Jim M.; Campbell, Dana L. M. (Frontiers in Veterinary Science, 2020)
Group-living can be socially advantageous where the behavior of individuals may be modified by group members through socially facilitative processes. Virtual fencing contains cattle by providing audio and electrical signals via a neckband device. However, little is known about social influences on learning to appropriately respond to the virtual fence (VF) cues. This study aimed to determine whether cattle respond to the behavior of conspecifics during their initial interactions with a VF across 3 days. Sixty-four Angus steers, naïve to virtual fencing, were placed into 8 paddocks (8 animals/group), divided with a VF into two areas- an inclusion and exclusion zone. The animals received an audio cue if they approached the VF followed by an electrical pulse if they continued into the exclusion zone. The GPS and audio and electrical stimuli data were recorded. To quantify social facilitation, individual VF interactions were grouped into 179 ‘events’ across 3 days; starting from when the first animal (leader) approached the VF. The responses of other animals were categorized as 1) followed the leader to move into the exclusion zone (followers, F), 2) accompanied the leader back into the inclusion zone (facilitated, Fa), 3) did not show any reaction (non-facilitated, NFa). A social facilitation score (SFaS) was calculated as SFaS (%) = (F/(Fa+NFa+F)) * 100. A single leader animal led on average 37% of events with 76.2% of all reactions categorized as facilitated by other individuals. Animals responded to the behavior of conspecifics more during the VF implementation compared with facilitated movement during natural grazing patterns when no VF was present (P < 0.001). On average, cattle stopped or turned away to 3.8 (± 2.9SE) audio cues before ever receiving their first electrical pulse. There was a positive correlation (R = 0.34, P = 0.006) between the number of audio cues received prior to the first electrical pulse and the proportion of all audio cues that were not followed by an electrical pulse. In conclusion, cattle stayed within the inclusion zone based on the response of conspecifics, including some social impacts on individual rates of associative learning between the audio and electrical cues.